Socialization agent’s knowledge dissemination among Bajau-Laut community : Tun Sakaran Marine Park Conservation Zone, Sabah - Noviatin Syarifuddin; Mohamad Fauzi Sukimi; Rahimah Abdul Aziz (Penerbit Universiti Kebangsaan Malaysia, 2018)
The issues of water conservation are part of the agenda of the Coral Triangle Initiative (CTI) between Malaysia, Indonesia and the Philippines due to the population of Bajau-Laut community in the surrounding waters. It is feared that the freedom of the communities living in the confines of our waters as well as cultivating their traditional fishing using explosives may threaten the sustainability of marine conservation zones. The knowledge and the preparation of the community to obey the rules and regulations enforced in the protected area of marine activity to ensure a sustainable supply for the future. Thus, this study aims to discuss the agents who socialize the knowledge of Bajau-Laut community about the conservation zone involving the Tun Sakaran Marine Park (TSMP). Research has been ongoing in Pulau Bum-Bum, Semporna, Sabah through applying phenomenological approaches on selected ten informants through purposive sampling techniques. Semi-structured interview was chosen to deepen the knowledge of Bajau-Laut community as the actor of the study. Assumptions made by ontology and epistemology idealist of the social constructivist envisioned paradigm study as a research to understand the significance of conservation zones that are formed from social reality of Bajau-Laut community. The results revealed that the Village Development Committee (JKKK), Welfare Association Bajau-Laut (PEKEBAL), the agency of Tun Sakaran Marine Park (TSMP) serves as a formal agent of socialization while families, friends and the media are informal socialization agents that make up the knowledge of informant. As a community living in an island, the knowledge of zoning and conservation efforts by the significant agencies is crucial to understand the importance of preserving habitat of marine resources. Hence, the habitat of marine resources could be protected and conserved for future supplies.